The Effectiveness of Halal Certification in Ensuring the Principle of Thaharah in Food Production: A Review from the Perspective of Islamic Economic Law - Zuhrotul; Biqi Zain (JIECIs - Journal of Islamic Economics and Contemporary Issues, 2026)
Halal certification functions as a legal instrument within the halal product assurance system aimed at providing certainty and protection for Muslim consumers; however, its effectiveness in ensuring the implementation of the principle of thaharah (ritual purity and cleanliness) in food production remains debatable. This study aims to analyze the effectiveness of halal certification in guaranteeing the application of the thaharah principle in food production from the perspective of Islamic economic law. This research employs a qualitative approach with a juridical-empirical design, combining normative analysis of halal-related regulations and fatwas with empirical data collected through in- depth interviews, direct observation of production processes, and document analysis involving halal-certified food business actors, halal process assistants, and halal auditors. The findings indicate that halal certification is effective in a normative and administrative sense, as reflected in compliance with legal and procedural requirements; however, it has not been fully effective substantively in consistently ensuring the application of thaharah principles in daily production practices. The results reveal that business actors’ limited understanding of thaharah, weak post-certification supervision, and the administrative orientation of halal certification are key factors affecting its effectiveness. This study concludes that halal certification tends to be perceived primarily as an administrative obligation, resulting in the incomplete realization of Islamic legal objectives, particularly the protection of religion and life. Therefore, strengthening the internalization of thaharah values, enhancing continuous supervision, and repositioning halal certification as a substantive instrument of Islamic economic law are necessary to improve its effectiveness.